Energy Democracies and Publics in the Making: A Relational Agenda for Research and Practice - Chilvers, Jason; Pallett, Helen (Frontiers in Communication, 2018)
Mainstream approaches to energy democracy and public engagement with energy transitions tend to adopt specific, pre-given meanings of both “democracy” and “publics.” Different approaches impose prescriptive assumptions about the model of participation, the identity of public participants, and what it means to participate well. The rigidity of many existing approaches to energy participation is increasingly being challenged by the ever-multiplying diversity of ways in which citizens participate in energy systems, as consumers in energy markets, protesters against new infrastructures and technologies, as initiators of community energy projects, and as subjects of behavior change interventions, amongst others. This paper is concerned with growing areas of scholarship which seek to understand and explore these emerging energy publics and forms of energy democracy from a relational perspective. Such work, grounded in constructivist and relational ontologies, views forms of participatory democracy and publics as being co-produced, constructed, and emergent through the performance of collective practices. It pays closer attention to power relations, politics, materiality, exclusions, and effects in both understanding and intervening in the making of energy democracy. This in turn shifts the focus from studying discrete unitary forms of “energy democracy” to one of understanding interrelations between multiple diverse energy democracies in wider systems. In this paper, we chart these developments and explore the significant challenges and potential contributions of relational approaches to furthering the theories, methods, and practices of energy democracy and energy public engagement. The paper draws on an expert workshop, and an accompanying review, which brought together leading proponents of contending relational approaches to energy participation in direct conversation for the first time. We use this as a basis to explore tensions between these approaches and set out a relational agenda for energy democracy research in terms of: developing concepts and theories; methodological and empirical challenges; and implications for practices of governance and democratic engagement with energy transitions.